Effect of CYP3A5 genotypes on pharmacokinetic of tacrolimus in colombian liver transplant patients - Erica Fernanda Lindarte; Erica Fernanda Lindarte; Gonzalo De Jesus Vasquez; Luis Guillermo Toro Rendón; Luis Guillermo Toro Rendón; Andrés Felipe Zuluaga Salazar; Andrés Felipe Zuluaga Salazar; Jefferson Antonio Buendia; Jefferson Antonio Buendia (Frontiers in Pharmacology)
BackgroundPrevious studies have reported a reduced tacrolimus dose-adjusted exposure in individuals expressing the CYP3A5*1 allele (rs 776746). However, information regarding Colombian liver transplantation patients is scarce. This study aimed to investigate the influence of CYP3A5 polymorphism on tacrolimus (TAC) pharmacokinetics in Colombian liver transplant patients.MethodsThis was a prospective, single-center, open-label, pharmacogenetic study in stable adult liver transplant recipients followed up between 2020 and 2022. To evaluate the longitudinal relationship between the Co/doses, dose, and Co and CYP3A5 polymorphisms, a generalized estimating equations model was used using a log-gamma distribution.ResultsWe evaluated 16 patients who received TAC during the first 2 years after transplantation. CYP3A5*1 expression was observed 28% of patients. Patients with CYP3A5 expressors displayed lower C0 and C0/dose ratio and higher doses than those no expressors. We observed a lower C0/dose ratio in expresser recipients over 2 years of follow-up.ConclusionThe expression of CYP3A5 in stable liver transplant patient appeared to have the greatest influence on tacrolimus pharmacokinetics over the first 2 years posttransplant.